2011
DOI: 10.1253/circj.cj-10-0759
|View full text |Cite|
|
Sign up to set email alerts
|

Restrictive Mitral Annuloplasty for Functional Mitral Regurgitation - Acute Hemodynamics and Serial Echocardiography -

Abstract: Background: Long-term effects of restrictive mitral annuloplasty (RMA), especially on hemodynamics and left ventricular (LV) function in patients with functional mitral regurgitation (MR), have not been fully investigated. Methods and Results:From 1999 to 2008, 44 patients with refractory heart failure and functional MR underwent RMA with stringent downsizing of the mitral annulus. Serial echocardiography was performed to evaluate LV function (reverse remodeling), estimated systolic pulmonary artery pressure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…4,5 The rationale for performing TVP, even in patients with TAD but without significant TR (TR 2þ), relies on evidence that TAD is an ongoing disease process that over time often leads to severe functional TR. 6 Although the effect of mitral valve surgery on left ventricular (LV) geometry and function in patients with severe mitral regurgitation (MR) has been extensively studied, [7][8][9][10][11][12][13] data on right ventricular (RV) geometry and function changes in response to TVP are surprisingly scarce. Although results have shown that mitral valve repair (MVP) induces reverse LV remodeling in a gradual and time-dependent fashion, it is not known whether TVP has similar beneficial effects on RV shape and function.…”
mentioning
confidence: 99%
“…4,5 The rationale for performing TVP, even in patients with TAD but without significant TR (TR 2þ), relies on evidence that TAD is an ongoing disease process that over time often leads to severe functional TR. 6 Although the effect of mitral valve surgery on left ventricular (LV) geometry and function in patients with severe mitral regurgitation (MR) has been extensively studied, [7][8][9][10][11][12][13] data on right ventricular (RV) geometry and function changes in response to TVP are surprisingly scarce. Although results have shown that mitral valve repair (MVP) induces reverse LV remodeling in a gradual and time-dependent fashion, it is not known whether TVP has similar beneficial effects on RV shape and function.…”
mentioning
confidence: 99%
“…In our study, rates of PVR ≥3 WU and PVR ≥5 WU were higher in patients with severe FMR. Although it is inconclusive whether treatment of severe FMR in patients with advanced heart failure will improve the outcome, it has been shown that it can reduce pulmonary pressures and PVR (21). Even treatment of severe FMR with ERO ≥0.4 cm 2 and RV ≥60 mL is controversial in these patients, it is very difficult to suggest to treat severe FMR at such a lower threshold.…”
Section: Discussionmentioning
confidence: 99%
“…This traditional hypothesis held that the mitral valve functions as a ''pop-off valve'' for the failing ventricle and surgical correction might have prohibitive risks in patients with severely remodeled LV because of postoperative afterload (systolic myocardial wall stress) excess and subsequent decline in LV ejection performance [3,11]. However, several recent studies showed that RMA procedure could induce reverse LV remodeling (decrease in LV volumes and increase in ejection fraction) after correction of MR in failing ventricle [15][16][17][18]. This controversial fact was partially settled by the previous publication from Takeda and colleagues which confirmed a strong association between the improvement in LV ejection fraction and the reduction in LV endsystolic wall stress in patients with advanced cardiomyopathy who received RMA procedure.…”
Section: Discussionmentioning
confidence: 99%